The Social Profile, Constraints, and Its Impact on Swine Herd Size in Tra Vinh Province, Vietnam - N. H. Qui; B. Guntoro; S. P. Syahlani (Faculty of Animal Science, Bogor Agricultural University, 2020)
The objective of this study was to describe social profile, constraints of swine farmers, and its impact on swine herd size in Tra Vinh Province. This study was conducted in Tra Vinh Province, one of the provinces in Mekong delta, Vietnam. A total of 120 swine farmers selected from small swine farms to commercial swine farms were surveyed with information gathered on 11,466 swine. All of the swine farmers in this study were purposively chosen and interviewed with the questionnaires for data collection. All swine farmers have kept at least 1 swine per farm or had experience at least 1 year for raising and trading swine. The results showed that the majority of farmers were males (57.5%), with the age range of 20-40 years old (47.5%), having more than 10 years of experience (52.5%), having 1-3 members in the family (87.1%), 85% of farmers focused on farm, farmers having livestock farming plus cropping accounted for 55.8%, and farmers having medium farm size with an average of 95-96 heads/farm. In addition, there were 4 constraints that farmers confirmed, i.e., capital (31.6%), disease outbreak (75%), low bargaining power (40%), and the fluctuation of feed price (59.16%). Moreover, experience (p<0.01), education (p<0.01), disease outbreak (p<0.05), and the fluctuation of feed price (p<0.05) had a strong influence on swine herd. It could be concluded that farmers having higher experience and education kept a larger number of swine than others. In contrary, when disease outbreak and the fluctuation of feed price emerge, farmers tended to control their swine herd size.